Optimization Of Information Systems for Resource Management in Mosques - Sultonudin, Muhamad Taufik; Supriatna, Ade; Supriatna, Haris; Jamaludin, Ikbal (LPPM STMIK Mardira Indonesia, 2024)
This study seeks to enhance the information system for resource management at Masjid Al-Qomar by implementing an application focused on financial and activity management. The applied research method is descriptive, applying an object-oriented system development approach (Object-Oriented Analysis and Design, OOAD). The developed system focuses on two main aspects: recording and reporting donations, including zakat and other financial activities, and managing schedules and communication with congregants. The research findings demonstrate that the suggested information system streamlines financial recording and reporting processes, improves transparency in fund utilization, and aids in financial reporting. This technology enhances the mosque's administrative efficiency through features including automated recording, readily available financial reports, and integrated activity schedule management. Furthermore, it guarantees that activity information is available to all congregants, including those not regularly attend the mosque, via an integrated platform and efficient communication tools. This research concludes that the effective implementation of an information system can augment financial transparency, promote operational efficiency, and elevate congregant participation. This study advocates for the ongoing enhancement and upkeep of the system to guarantee its performance aligns with the mosque's and its users' requirements.